Novel Insights Into the Potential Mechanisms of N6-Methyladenosine RNA Modification on Sepsis-Induced Cardiovascular Dysfunction: An Update Summary on Direct and Indirect Evidences - Wang, Yang; Xu, Miaomiao; Yue, Peng; Zhang, Donghui; Tong, Jiyu; Li, Yifei (Frontiers in Cell and Developmental Biology, 2021)
Sepsis is a life-threatening organ dysfunction caused by a host's dysfunctional response to infection. As is known to all, septic heart disease occurs because pathogens invading the blood stimulate the activation of endothelial cells, causing a large number of white blood cells to accumulate and trigger an immune response. However, in severe sepsis, the hematopoietic system is inhibited, and there will also be a decline in white blood cells, at which time the autoimmune system will also be suppressed. During the immune response, a large number of inflammatory factors are released into cells to participate in the inflammatory process, which ultimately damages cardiac myocytes and leads to impaired cardiac function. N6-methyladenosine (m6A) is a common RNA modification in mRNA and non-coding RNA that affects RNA splicing, translation, stability, and epigenetic effects of some non-coding RNAs. A large number of emerging evidences demonstrated m6A modification had been involved in multiple biological process. Especially for sepsis and immune disorder diseases. Unfortunately, there is limited results provided to analysis the association between m6A modification and SICD. In this review, we firstly summarized current evidences on m6A mediates the pathophysiological process in cardiac development and cardiomyopathy to emphasize the importance of RNA methylation in maintain heart biogenesis and homeostasis. Then we clarified the participants of m6A modification in extended inflammation responses and immune system activation, which is the dominant and initial changes secondary to sepsis attack. After that we deeply analyzed the top causes of SICD, and identified activation of inflammatory cytokines, endothelial cells dysfunction and mitochondrial failure. Thus, the highlights of this review is that we systematically collected all the related potential mechanisms between m6A modification and SICD causes. Although there is lacking of direct evidences on SICD, but indirect evidences had been demonstrated case by case on every particular molecular mechanisms and signaling transduction, which requires the further explorations into the potential links among the listed mechanisms. it provides novel insights into the understanding of SICD.